Evaluating the impact of clinical and translational pilot funding using multiple outcome metrics - Ingrid Philibert; Angela Batson; Amanda Fletcher (Journal of Clinical and Translational Science)
NIH/NIGMS-funded IDeA-Clinical and Translational Research (CTR) networks seek to expand translational research infrastructure to support research that has at its endpoints measurable clinical, public health, technological, or economic benefits. This retrospective case study followed 14 projects that received Pilot funding from the Great Plains IDeA-CTR (GP IDeA-CTR) at the University of Nebraska Medical Center. It focuses on the impact of pilot funding and GP IDeA-CTR resources on subsequent clinical and translational research. Metrics include extramural awards, lessons learned that relate to clinical and translational research infrastructure, and demonstrated and potential benefits using the Translational Science Benefits Model (TSBM).